Changes in molecular characteristics and antimicrobial resistance of invasive Staphylococcus aureus infection strains isolated from children in Kunming, China during the COVID-19 epidemic - Ma, Mingbiao; Tao, Lvyan; Li, Xinyue; Liang, Yanqi; Li, Jue; Wang, Haiping; Jiang, Hongchao; Dong, Jing; Han, Dingrui; Du, Tingyi (Frontiers in Microbiology, 2022)
Invasive Staphylococcus aureus (S. aureus) infection is associated with high rates of mortality in children. No studies have been reported on invasive S. aureus infection among children in Kunming, China, and it remains unknown whether the COVID-19 epidemic has affected S. aureus prevalence in this region. Thus, this study investigated the changes in molecular characteristics and antimicrobial resistance of invasive S. aureus strains isolated from children in Kunming during 2019-2021. In total, 66 invasive S. aureus strains isolated from children were typed by multilocus sequence typing (MLST), spa, and SCCmec, and antimicrobial resistance and virulence genes were analyzed. A total of 19 ST types, 31 spa types and 3 SCCmec types were identified. 39 (59.09%) strains were methicillin-sensitive S. aureus (MSSA) and 27 (40.91%) strains were methicillin-resistant S. aureus (MRSA). The most common molecular type was ST22-t309 (22.73%, 15/66), followed by ST59-t437 (13.64%, 9/66). In 2019 and 2021, the dominant molecular type was ST22-t309, while in 2020, it was ST59-t437. After 2019, the dominant molecular type of MRSA changed from ST338-t437 to ST59-t437. All strains were susceptible to tigecycline, ciprofloxacin, moxifloxacin, vancomycin, quinopudine-dafoputin, linezolid, levofloxacin, and rifampicin. From 2019 to 2021, the resistance to penicillin and sulfamethoxazole initially decreased and then increased, a trend that contrasted with the observed resistance to oxacillin, cefoxitin, erythromycin, clindamycin, and tetracycline. Sixteen antimicrobial resistance profiles were identified, with penicillin-tetracycline-erythromycin-clindamycin-oxacillin-cefoxitin being the most common, and the antimicrobial resistance profiles varied by year. The carrier rates of virulence genes, icaA, icaD, hla, fnbA, fnbB, clfA, clfB, and cna were 100.00%. Furthermore, sak, pvl, icaC, icaR, fib, lip, hlb, hysA, sea, seb, and tsst-1 had carrier rates of 96.97%, 92.42%, 87.88%, 69.70%, 84.85%, 62.12%, 56.06%, 50%, 37.87%, 30.30%, and 7.58%, respectively. Since COVID-19 epidemic, the annual number of invasive S. aureus strains isolated from children in Kunming remained stable, but the molecular characteristics and antimicrobial resistance profiles of prevalent S. aureus strains have changed significantly. Thus, COVID-19 prevention and control should be supplemented by surveillance of common clinical pathogens, particularly vigilance against the prevalence of multidrug-resistant and high-virulence strains.